KEDUDUKAN HUKUM KEPEMILIKAN HARTA PAILIT YANG BERASAL DARI PPJB YANG DIKONVERSI MENJADI SAHAM PT: STUDI PUTUSAN PENGADILAN NEGERI NO. 29/PDT.SUS-GLL/2022/PN.NIAGA.JKT.PST - Nurjannah, Lia; Sunarmi, Sunarmi; Siregar, Mahmul (Penerbit Lafadz Jaya, 2026)
The curator must be responsible for any errors or negligence in carrying out management and/or settlement obligations that cause losses or reduction in the value of bankrupt assets. Therefore, the curator will take over legal cases concerning the assets of the bankrupt debtor, in accordance with the provisions of Article 26 paragraph (1) of Law No. 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations. The objectives of this thesis include analyzing the legal consequences of the transfer of rights based on the PPJB which are then converted into shares, analyzing the legal status of ownership of bankrupt assets originating from the PPJB converted into shares, and analyzing the judge's considerations in the District Court decision No. 29/Pdt.SUS-GLL/2022/PN.Niaga.Jkt.Pst. The type of research used is Normative Legal Research. Normative legal research is carried out using a statute approach and a case approach. The data sources used are Primary Legal Materials (written rules enforced by the state), Secondary Legal Materials (materials in the form of legal reviews), and Tertiary Legal Materials (materials that support both primary and secondary legal materials). Data collection techniques are through literature studies of legal materials (rechtsmaterialen) and field research through direct interviews with; Commercial Judges of the Medan District Court, Curators, and Notaries. The results of this thesis research can be concluded firstly that PPJB should not be convertible into PT shares because the PPJB has not yet had a physical and juridical handover. Secondly, the curator will represent the bankrupt debtor in all matters related to the settlement and management of bankrupt assets, including representing the bankrupt debtor in every lawsuit filed either by or against third parties for and on behalf of the bankrupt debtor. The judge's three considerations in the decision were to sentence and order the Defendant (Curator) to remove the plaintiff's immovable assets from the Bankruptcy Asset List, as well as to remove them from all documents related to the bankrupt assets (budel) and to declare that the Curator had committed an Unlawful Act (PMH).